IMPLEMENTAÇÃO DE BOAS PRÁTICAS DE ATENÇÃO AO PARTO E NASCIMENTO EM UMA UNIDADE OBSTÉTRICA - Pereira, Simone Barbosa (2016)
Good practices in childbirth and birth care do not constitute a new theme. They have gained notoriety due to the excessive use of invasive technologies and a high number of cesarean sections, in which Brazil ranks first in the world scale. One of the drivers of these changes was the launch by the World Health Organization in 1985 of the document entitled "Appropriate technologies for childbirth and birth". This document has promoted the adoption of good practices in care delivery and birth, capable of breaking with traditional models of intervention at delivery and birth, through new methodologies and intervention technologies aimed at the humanization of childbirth. Based on this proposal, the present study aimed as its general objective: To implement the good practices of attention to childbirth and birth, recommended by the World Health Organization, in a medium-sized Hospital Obstetric Unit. As specific objectives, this study considered: Know the professionals' perception professionals of an obstetric hospital unit on the good practices of attention to childbirth and birth, recommended by the World Health Organization; and, Describe the construction and validation steps of a construct of good practices of attention to childbirth and birth, to be implemented in an Obstetric Unit of habitual risk. In order to meet the first specific objective, a qualitative research was carried out, using the focal group technique, with the participation of the multidisciplinary team of the Obstetric Unit of habitual risk, of a medium-sized institution, from April to June 2016. The second specific objective was taken from a methodological survey, carried out between August and October 2016, with the participation of 12 judges from the obstetric area, national level, between the first and second round Delphi. From the data resulting from the first specific objective and codified by content analysis, three thematic categories emerged: good practices and their meanings; from the biological character to the singular and multidimensional care; from the punctual and fragmented conception to the network of attention to childbirth and birth. It was concluded that good practices in childbirth care and birth, in addition to making it possible to rethink the obstetric model and contribute to the organization of the maternal and child health care network, stimulate the role of women in their multiple dimensions. In response to the second specific objective, was obtained, in the judges' analysis, a return of 12 instruments evaluated in the first round and seven instruments in the second round Delphi. In the first round, significant suggestions for changes were made in relation to the items of the dimensions of the construct, in which the judges presented convergences in relation to the mission, vision and values, but suggested changes in the item "assignments of each professional in the team". The construct was considered valid, both in content and appearance, and could contribute to subsidize good practices of attention to childbirth care and birth in local and national territory. It is concluded that, besides the governmental initiatives, it is necessary that the health professionals are responsible for and assume the good practices of attention to childbirth and birth as a possibility of transformation of the obstetric model. As a way of broadening the reflections and qualifying the good practices of attention to childbirth and birth at the Obstetric Unit, the origin institution of the principal researcher, she presented to the managers and multi professional team the validated construct, in days and at times previously scheduled. In addition, a graphical representation of the Construct of Good Practices of Attention to Childbirth and Birth, validated by the Judges of the obstetric area, was prepared, which will be exposed at the main entrance of the Obstetric Unit in question.